Windfall gains and house money: The effects of endowment history and prior outcomes on risky decision–making - Hauke Jelschen; Ulrich Schmidt (Journal of Risk and Uncertainty, 2023)
In a seminal contribution, Thaler and Johnson ( 35 ) detected the existence of a house money effect which is defined as an increase in risk tolerance after previous gains resulting from a risky activity. Subsequent studies used the term house money effect also in case of windfall gains, i.e., easily acquired money like show-up fees or initial endowments in experiments which does not result from a risky investment. The present study is to the best of our knowledge the first that disentangles the house money effect and windfall gains. We find a clear and systematic pattern that windfall gains increase risk tolerance. In contrast, the house money effect is far less ubiquitous and seems to require skewed lotteries and/or a large number of rounds played. We, therefore, conclude that a careful distinction between windfall gains and the house money effect is warranted in future research.
Keywords: C91; D81; 300; House money effect; Windfall gains; Risk aversion; Quasi-hedonic editing; Prospect theory